1998
DOI: 10.1016/s0378-4290(97)00039-7
|View full text |Cite
|
Sign up to set email alerts
|

Durations of the photoperiod-sensitive and -insensitive phases of time to panicle initiation in sorghum

Abstract: The development of sorghum [Sorghum bicolor (L.) Moench] is influenced by genes that control sensitivity to photoperiod, and their interaction with photoperiod and temperature. While temperature influences development throughout the life cycle of plants, photoperiod influences the vegetative stage (from seedling emergence to panicle initiation). In order to simulate plant development, it is essential to know when sorghum plants first become sensitive to photoperiod, and how long that photoperiod sensitivity pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
2
13
2
1
Order By: Relevance
“…Magalhães et al (2000) reported that sowing delays and low temperatures may decrease metabolic activities and thus plants may extend their cycle. Therefore, it can be inferred that this material is sensitive to photoperiodic variations, what was already found by Paul (1990) and Alagarswamy et al (1998).…”
Section: Resultssupporting
confidence: 73%
“…Magalhães et al (2000) reported that sowing delays and low temperatures may decrease metabolic activities and thus plants may extend their cycle. Therefore, it can be inferred that this material is sensitive to photoperiodic variations, what was already found by Paul (1990) and Alagarswamy et al (1998).…”
Section: Resultssupporting
confidence: 73%
“…These distinct behaviors are due to differences in the model parameterization of sorghum's photoperiod sensitivity. Sorghum is a short‐day plant; i.e., it develops more rapidly on short days [ Major , ], and this photoperiod sensitivity usually occurs prior to floral initiation [ Alagarswamy et al , ]. APSIM adopts a linear relationship between plant thermal requirements (i.e., growing degree day, GDD) and day length [ Kumar et al , ] and uses field phenology observation to calibrate the parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Sorghum phenology is modeled by recognizing a series of phases delimited by stages that include seedling emergence, end of juvenile phase (phase when plants are insensitive to photoperiod; Alagarswamy et al, 1998), panicle initiation, end of leaf expansion, anthesis, and physiological maturity (Table 2). Phenology is simulated in the routine SG_PHENOL.FOR.…”
Section: Methodsmentioning
confidence: 99%